1965
DOI: 10.1083/jcb.25.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The Mitotic Apparatus

Abstract: Previous investigations have shown that the mitotic apparatus (MA) can be isolated from dividing sea urchin eggs in water buffered at pH 5.6 and that the addition of 1 M hexanediol to the solution raises the usable pH to 6.4. Long chain glycols appeared to be much more effective than related compounds in increasing the stability of the MA, and the aim of the investigations reported here was to determine the basis of this specificity. These experiments show that this impression of specificity is misleading and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

1966
1966
2000
2000

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 12 publications
(20 reference statements)
1
31
1
Order By: Relevance
“…A totally different procedure for the preparation of 22S protein, not involving organic solvents, may shed some light on the question. Mazia et al (1961 b) have shown spindle isolates to be stabilized by the presence of dithiodiglycol, while Kane ( a, 1965 has demonstrated that many glycols not containing the disulfide linkage serve the same purpose. However, the dithiodiglycol isolates are generally more Where molecular weight determinations were carried out, the molecular weight is indicated in terms of multiples of "n," the average weight of the smallest subunit thus far obtained (1 l~,000).…”
Section: Discussion the 2 2 S Particlementioning
confidence: 99%
See 3 more Smart Citations
“…A totally different procedure for the preparation of 22S protein, not involving organic solvents, may shed some light on the question. Mazia et al (1961 b) have shown spindle isolates to be stabilized by the presence of dithiodiglycol, while Kane ( a, 1965 has demonstrated that many glycols not containing the disulfide linkage serve the same purpose. However, the dithiodiglycol isolates are generally more Where molecular weight determinations were carried out, the molecular weight is indicated in terms of multiples of "n," the average weight of the smallest subunit thus far obtained (1 l~,000).…”
Section: Discussion the 2 2 S Particlementioning
confidence: 99%
“…difficult to dissolve in neutral salt than their hexylene glycol counterparts and both become insoluble on standing (Dirksen, 1964;Kane and Forer, 1965), requiring the use of either high pH or sulfhydryl reagents for solubilization. In this study, the 22S protein, even in high salt, will form aggregates when either sulfhydryl or disulfide compounds are present.…”
Section: Discussion the 2 2 S Particlementioning
confidence: 99%
See 2 more Smart Citations
“…12). Several other proteins (19) and protein structures (20,21) also show increased stability in glycols.…”
Section: Concentrcflion Of Kci (M)mentioning
confidence: 99%